A randomised, controlled, crossover study to investigate the pharmacodynamics, pharmacokinetics and safety of 1R, 2S‐methoxamine hydrochloride (NRL001) in healthy elderly subjects. (March 2014) - Bell, D.; Duffin, A.; Gruss, H. J.; Pediconi, C.; Jacobs, A.
Abstract: Aims: This study aimed to assess the effects of a single dose of 10 mg NRL001 (the 1R, 2S stereoisomer of methoxamine hydrochloride) in a 2 g suppository on pharmacodynamic and pharmacokinetic (PK) variables, and safety, in a healthy elderly population. Methods: This was a Phase I, single‐centre, randomised, double‐blind, placebo‐controlled crossover study during which subjects received a single 2 g suppository of 10 mg NRL001 and a matching placebo in two separate treatment periods. The main outcome measures were Holter‐, vital signs‐ and electrocardiogram‐derived cardiovascular variables; plasma PK analysis; and safety assessments. Results: Twenty‐six subjects were dosed with study medication. Statistically significant reductions in Holter‐derived heart rate (HR), vital signs‐derived HR and diastolic blood pressure (BP) were observed comparing NRL001 with placebo treatment, and also with increasing NRL001 plasma concentration. No statistically significant relationships were observed between NRL001 concentration and systolic BP, mean arterial pressure or QTC interval (both Bazett's and Fridericia's correction). Thirty‐nine adverse events were reported in 20 (76.9%) subjects, mostly after dosing with NRL001. Conclusion: Administration of NRL001 suppositories led to decreases in HR when compared with placebo data. NRL001 was well tolerated with a good safety profile during the study. Healthy elderly subjects did not show significantly different biological responses to NRL001 suppositories compared with younger healthy volunteers in previous studies.